Happy Translation and the Now of Recognizability: Walter Benjamin’s 1936 Dialogue - Brooks, Andrew (Culture as Text, 2025)
This paper explores Walter Benjamin’s lesser-known 1936 essay, “La traduction – le pour et le contre,” and its critical role in understanding his late materialist theory of translation. This paper demonstrates a form of Benjamin’s “happy translation,” as a mode of close reading through re-translation with commentary. While “The Task of the Translator” (1921) remains his most comprehensive work on the subject, the 1936 essay signifies a shift towards a materialist aesthetic theory, introducing concepts such as “happiness,” “Technik,” and the “now-of-recognizability.” By contextualizing the essay within Benjamin’s Paris exile and examining the philosophical and historical influences, including his complex relationship with Nietzsche’s works, this paper argues that Benjamin’s 1936 essay marks a transition to an atemporal, non-linear translation theory. This shift is embodied by the allegorical figure of the flâneur, highlighting the relational and revolutionary potential of translation as a cunning form that brings about the “now-of-recognizability.”